2016
DOI: 10.1097/adm.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Using a Learning Collaborative Strategy With Office-based Practices to Increase Access and Improve Quality of Care for Patients With Opioid Use Disorders

Abstract: Objectives Rapidly escalating rates of heroin and prescription opioid use have been widely observed in rural areas across the United States. Although US Food and Drug Administration-approved medications for opioid use disorders exist, they are not routinely accessible to patients. One medication, buprenorphine, can be prescribed by waivered physicians in office-based practice settings, but practice patterns vary widely. This study explored the use of a learning collaborative method to improve the provision of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…This model links primary care providers with larger OMT programs to provide support and guidance for patient management, and providers a nurse and case manager for primary care clinics (Simpatico, 2015). Together with alearning collaborative (Nordstorm et al, 2016), the: hub-and-spoke approach has shown demonstrable gains in engaging physicians and increasing buprenorphine adoption. A second approach is use of telemedicine or teleconsultation to link inexperienced providers with mentors to help navigate buprenorphine OMT procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This model links primary care providers with larger OMT programs to provide support and guidance for patient management, and providers a nurse and case manager for primary care clinics (Simpatico, 2015). Together with alearning collaborative (Nordstorm et al, 2016), the: hub-and-spoke approach has shown demonstrable gains in engaging physicians and increasing buprenorphine adoption. A second approach is use of telemedicine or teleconsultation to link inexperienced providers with mentors to help navigate buprenorphine OMT procedures.…”
Section: Discussionmentioning
confidence: 99%
“…To support state-wide dissemination and implementation of the hub-and-spoke model and establish consistency in all practices, a learning collaborative was developed (Nordstrom et al, 2016). It offers in-person and web-based lectures to spoke physicians and MAT staff covering safe prescribing, use of evaluation tools, treatment plan development, responses to relapse, patient noncompliance, and diversion control.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, teams were developed that were comprised generally of a nurse and behavioral health specialist that support the clinicians by conducting patient intakes/assessments and then manages many other ongoing treatment activities (e.g., delivers counseling, arranges for urine toxicology testing). Finally, a centralized learning collaborative has been developed that offers ongoing training on evidence-based practices [81]. The opportunity to develop and sustain this model of care is the result of forward-thinking state legislation working closely with clinical experts along with a favorable insurance/Medicaid landscape in Vermont.…”
Section: Models Of Care For Medication Treatmentsmentioning
confidence: 99%